Karakater Hamba Tuhan Menurut 1 Timotius 6:11-12 - Sukarno Hadi (Sabda: Jurnal Teologi Kristen, 2020)
Character is one of the elements related to the principles and values of life that influence a person's thoughts, attitudes and behavior. To be a servant of God is a call from God personally to the person He wants. Many servants of God lose the focus of their ministry and lose God's character in their lives. A pastor in ministry must have the character of a servant of GodThe method in writing scientific papers is descriptive qualitative using literature study. The concept of the character of God's servants in 1 Timothy 6: 11-12, namely: First, stay away from all forms of evil. All forms of crime such as arrogance or pretending to be ignorant, looking for questions and fighting words that cause envy, injury, slander, suspicion, and bickering, wrong motivation in worship (1 Tim. 6: 4-5), greed / greed that is shown love of money (1 Tim. 6: 9-10. Second, pursuing all forms of virtue, which are the principles and nature of serving God and others. The first form of virtue is justice. Timothy must pursue justice, worship or piety, faithfulness, love. , patience, gentleness (1 Tim. 6:11), Third, defend his vocation by competing in a good / true faith contest (1 Tim. 6:12) Keywords: Concept, Character, Servant of God. Abstrak Karakter adalah salah satu unsur  yang terkait dengan prinsip dan nilai hidup yang mempengaruhi pikiran, sikap, serta perilaku seseorang. Menjadi hamba Tuhan adalah sebuah panggilan dari Allah secara pribadi kepada orang yang dikehendakiNya. Banyak hamba-hamba Tuhan kehilangan fokus pelayanan dan kehilangan karakter Allah dalam kehidupannya. Seorang gembala dalam pelayanan harus  memiliki karakter hamba TuhanMetode dalam penulisan karya ilmiah ini adalah deskriptif kualitatif dengan menggunakan studi pustaka . Konsep tentang  karakter hamba Tuhan dalam 1 Timotius 6:11-12 yaitu:Pertama, menjauhi segala bentuk kejahatan. Segala bentuk kejahatan seperti kesombongan atau berlagak tahu, mencari-cari soal dan bersilat kata yang menyebabkan dengki, cidera, fitnah, curiga, dan percekcokan, motivasi yang salah dalam beribadah (1 Tim. 6:4-5), keserakahan/ketamakan yang ditunjukkan cinta uang (1 Tim. 6:9-10.Kedua, mengejar segala bentuk kebajikan, yang menjadi prinsip dan sifat dasar dalam melayani Tuhan dan sesama. Bentuk kebajikan yang pertama adalah keadilan. Timotius harus mengejar keadilan , ibadah atau kesalehan, Kesetiaan. kasih, kesabaran, kelemah-lembutan (1 Tim.6:11), Ketiga, mempertahankan panggilannya dengan cara bertanding dalam pertandingan iman yang baik/benar (1 Tim.6:12) Kata kunci: Konsep, Karakter, Hamba Tuhan.